Effectiveness of Students’ Vocabulary Mastery Using the Comic “Donald Duck” in Junior High School - Putri, Marcell Ghangsar; Yulianti, Fitri; Suwarti, Tarcisia Sri (Institut Agama Islam Sunan Giri Ponorogo, 2023)
This research was focused on investigating the effectiveness of students' vocabulary mastery using the comic